(untitled) (Impetus, 2025)
Quadball is a mixed contact sport that originated in the United States in 2005 and is inspired by the Harry Potter literary saga. Already established throughout the planet, it is currently going through a process of change and transformations, to whose understanding we aspire to contribute here. Thus, the objective of this work is, recovering the point of view of the actors, to analyze the challenges faced by practitioners of this sport in Argentina at this stage. We will focus on competition, a factor that has been considered by other authors as denaturalizing this practice and we take the idea of ​​recreational and competitive sport as a reference for the investigation. To achieve this, we will resort to the ethnography carried out among Argentine players between 2018 and 2022, carrying out a methodological triangulation with the CPRD-F, which was applied in 2023. In this way, we aspire to reconstruct the point of view of the actors about this process of change.